MINISTRY of GENEROSITY - A proposal for the Democratization of Prosperity fostering the CULTURE of GENEROSITY - Vicente Pironti (International Journal of Educational Evaluation and Policy Analysis, 2024)
This thesis examines the critical role of education in societal transformation, drawing on Werner Jaeger's assertion that the state is the primary agent of education and cultural evolution. In "Paideia," Jaeger emphasizes the state's role in shaping individual development and humanity's essence through educational systems. The thesis introduces the concept of a Ministry of Generosity, a state initiative aimed at fostering a Culture of Generosity as a formal measure of societal happiness. This ministry would integrate the Pedagogy of Generosity into education, promoting prosperity and compassion across economic and educational spheres. The thesis explores the General Theory of Generosity and its practical application in social and educational technology, highlighting the pioneering work of Dr. hc Vicente Pironti, founder of Humaniza. It examines how these technologies can drive cultural transformation and set a global standard for education and societal well-being. Additionally, the thesis addresses the development of humanized algorithms within the Artificial Intelligence Universe, incorporating ethical parameters and compassion for humans, sentient beings, and the environment. These humanized algorithms are presented as a crucial element in realizing the new Culture of Generosity.